The Palgrave Handbook of Audiovisual Translation and Media Accessibility - Bogucki, Łukasz; Deckert, Mikołaj (Palgrave Studies in Translating and Interpreting, 2020)
XXIV, 739 p. 29 illus., 4 illus. in color.